2014
DOI: 10.1590/s0080-623420140000600010
|View full text |Cite
|
Sign up to set email alerts
|

Living with pain: the experience of children and adolescents in palliative care

Abstract: El estudio tuvo como objetivo conocer la experiencia de niños y adolescentes en cuidados paliativos en el manejo diario del dolor. La investigación cualitativa fue realizada con entrevistas semi-estructuradas con seis niños entre siete y 17 años. La teoría del Desarrollo cognitivo de Piaget fue utilizada como Marco teórico y la Historia Oral como Referencial Metodológico. Cuatro temas fueron encontrados: describiendo el dolor; buscando una vida más próxima de la normalidad, a pesar del dolor y la enfermedad; u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…A qualitative study pointed out that children in the pre-operating stage of development described their pain emphasizing sensitive and evaluative aspects, which may indicate the characteristic of this phase in which the children have premature symbolic representation 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A qualitative study pointed out that children in the pre-operating stage of development described their pain emphasizing sensitive and evaluative aspects, which may indicate the characteristic of this phase in which the children have premature symbolic representation 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Studying the pain of children/adolescents studies show that from the age of 4, children are capable of describing their pain through sensitive descriptors in the same way as it is described by older children or adults 3 , 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain characteristics-from the perspective of children Borghi et al (2014) Perquin et al (2003 1. "It hurts when the bandage is removed, it is a pain that hurts, it is a pain that pulls, it makes me cry and it is tiring.…”
Section: Results (Current and Past Experiences Of Pain In Children)mentioning
confidence: 99%
“…In 1971, children's subjective pain perceptions were studied for the first time, and the results revealed that children could describe the nature of their pain verbally or through drawings (Schultz, ). Recent clinical research studies have made major contributions to expand this body of knowledge of pain in children, clarifying how children cope with acute and chronic pain ( Meldrum, Tsao, & Zeltzer, ; Borghi, et al, ; Pope, Tallon, McConigley, & Wilson, ; Smith, et al, ), cognitive and emotional aspects of pain (Kortesluoma, Nikkonen, & Serlo, ; Kortesluoma, Punamäki, & Nikkonen, ), describing pain experiences with drawings (Jongudomkarn, Aungsupakorn, & Camfield, ; Unruh, McGrath, Cunningham, & Humphreys, ) and children's perceptions of pain (Chaves, et al, ). Literature keeps growing in this subject area covering different aspects of pain in children (Kortesluoma & Nikkonen, ; Meldrum, et al, ; Neuman, ; Pölkki, Pietilä, & Vehviläinen‐Julkunen, ; Pölkki, Rissanen, & Pietilä, ).…”
Section: Introductionmentioning
confidence: 99%